Denture Microbiome Shift And Changes Of Salivary Inflammatory Markers Following Insertion Of 3d Printed Removable Partial Pmma Denture: A Pilot Study - Norlela Yacob; Syarida Hasnur Safii; Norasmatul Akma Ahmad; Norsiah Yunus; Fathilah Abdul Razak (Springer Nature, 2024)
Indexed by WOS/Scopus/ERA